Telaah Buku Teks Bahasa Arab Kelas VI Erlangga Berdasarkan Teori W.F Mackey - Fakhruroji, Zanuba Barqiati Hasfat; Ramadanti, Fathiya Muthmainah; Rahmawati, Siti Uriana; Umbar, Kisno (Ta'limi | Journal of Arabic Education and Arabic Studies, 2025)
This study aims to analyze the feasibility of the textbook “Semangat Belajar Bahasa Arab untuk MI Kelas VI by A. Saehudin” based on W.F. Mackey's theory, which includes the criteria of selection, gradation, presentation, and repetition of materials. The research employs a descriptive qualitative approach, with the main sources being content analysis of the Erlangga Kurikulum Merdeka Grade VI textbook and an evaluation of its alignment with W.F. Mackey's theory. The results of the study indicate that the textbook fulfills the selection criteria, with materials relevant to learning objectives, students' proficiency levels, learning time duration, the type of language being studied, and the feasibility of the materials being learned. In terms of gradation, the material is organized in a logical sequence from basic to complex skills. The presentation of the material is contextual but shows weaknesses in its visual aspects. The repetition aspect is sufficiently effective, as evidenced by repetitive exercises and supporting media such as audio materials. The conclusion of the study confirms that this textbook can support Arabic language learning in Madrasah Ibtidaiyah. Recommendations are provided to improve the visual quality and diversify the material presentation to make it more engaging and relevant for students.